Argemone mexicana leaf extract for inhibition of mild steel corrosion in sulfuric acid solutions - Ji G.; Shukla S.K.; Ebenso E.E.; Prakash R. (My University, 2025)
Inhibition potential of Argemone mexicana leaf extract (AMLE) for corrosion inhibition of mild steel in 0.5 M H2SO4 has been determined by weight loss, Tafel polarization and electrochemical impedance spectroscopy techniques. It is found from the results of weight loss method that inhibition efficiency of AMLE increases in concentration dependent manner which is also supported by the results of electrochemical techniques. Maximum inhibition efficiency of 87% has been achieved using 600 mg L-1 of inhibitor. Adsorption behavior of AMLE has been studied and it is found to be described most suitably by Langmuir isotherm. Organic moieties present in extract are found responsible for effective performance of inhibitor which is well supported by optical microscopy and FTIR studies. © 2013 by ESG.